2019
DOI: 10.21595/vp.2019.21175
|View full text |Cite
|
Sign up to set email alerts
|

Effect of in-wheel motor suspension system on electric vehicle ride comfort

Abstract: This paper presents the effect of in-wheel motor (IWM) suspension system on electric vehicle (EV) ride comfort. To analyze the impact on the vehicle ride comfort caused by IWM suspension system, a dynamic model of quarter vehicle is established with the combination of IWM and road surface roughness excitations. The weighted root-mean-square (r.m.s.) acceleration of the vertical vehicle body () according to the international standard ISO 2631-1 (1997) is selected as an objective function to analyze the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 10 publications
0
0
0
Order By: Relevance
“…Designing a sliding mode controller for both the suspension and the TMD is an effective method for improving ride comfort and suppressing vibrations, as demonstrated by the suggested method, which showed better response in vibration management and led to improved ride comfort and road-holding. The study in [121] analyzed the effects of IWM on vehicle stability, safety, and ride comfort based on a quarter vehicle suspension model. During simulations, the occurrence of wheel hop, which is dependent on unsprung mass and tire stiffness, was monitored.…”
Section: Unsprung Massmentioning
confidence: 99%
See 1 more Smart Citation
“…Designing a sliding mode controller for both the suspension and the TMD is an effective method for improving ride comfort and suppressing vibrations, as demonstrated by the suggested method, which showed better response in vibration management and led to improved ride comfort and road-holding. The study in [121] analyzed the effects of IWM on vehicle stability, safety, and ride comfort based on a quarter vehicle suspension model. During simulations, the occurrence of wheel hop, which is dependent on unsprung mass and tire stiffness, was monitored.…”
Section: Unsprung Massmentioning
confidence: 99%
“…Ref. [121] analyzed the impact of an in-wheel motor (IWM) suspension system on the ride comfort of electric vehicles (EVs) by considering various road surface roughness and IWM mass conditions. The study found that the IWM suspension system significantly improved EV ride quality, reducing the weighted root-mean-square acceleration of the vertical vehicle body by 8.6% compared to without the IWM suspension system.…”
Section: Eccentricitymentioning
confidence: 99%